Persepsi Warga Sekolah MTs Al-A’dhami Sendang Pragaan Sumenep terhadap Kepemimpinan Kepala Kantor Kementerian Agama Sumenep - Ahmadi Ahmadi; Masrufah Masrufah (Maharot : Journal of Islamic Education, 2020)
This article reveals the perception of the residents of MTs Al-A'dhami Sendang Pragaan Sumenep school towards the leadership of the Head of the Sumenep Ministry of Religion Office in managing education in Sumenep district. This research uses qualitative methods, case studies. From the research process, it was found that the residents of the MTs Al-A'dhami Sendang Pragaan Sumenep school had positive and negative perceptions of the leadership of the Head of the Office of the Ministry of Religion in Sumenep. This perception is based on the stimulus received by the five senses of the school community. Even though the two perceptions, especially the negative ones, are often caused by the ignorance of the school community about this.Â